Profiling UiTM Digital Library Initiatives : Perpustakaan Tun Abdul Razak - UiTM, Perpustakaan Tun Abdul Razak (Perpustakaan Tun Abdul Razak, 2022)
Perpustakaan Tun Abdul Razak (PTAR). UiTM is committed to realizing the aspirations of Universiti Teknologi MARA (UiTM) to continue achieving excellence and enhancing UiTM at the global level.